Fluorescence Resonance Energy Transfer (FRET) as a method to calculate the dimerization strength of basic Helix-Loop-Helix (bHLH) proteins - Centonze, Victoria E. (Biological Procedures Online, 2004)
Post-translational modifications such as phosphorylation play a vital role in the regulation of protein function. In our study of the basic Helix-loop-Helix (bHLH) transcription factor HAND1, we show that HAND1 is phosphorylated during the trophoblast giant cell differentiation on residues residing in Helix I of the bHLH domain. Our hypothesis is that these modifications result in changes in HAND1 dimerization affinities with other bHLH factors. To test this idea, we employed FRET to measure the protein-protein interactions of HAND1 and HAND1 point mutants in HEK293 cells using YFP and CFP fusion proteins and laser scanning confocal microscopy.